Degradation, solubility and chromatographic studies of Ibuprofen under high temperature water conditions. (August 2021) - Akay, Sema; Öztürk, Serpil; Kalderis, Dimitrios; Kayan, Berkant
Abstract: Ibuprofen (IBP) is an emerging environmental contaminant having low aqueous solubility which negatively affects the application of advanced oxidation and adsorption processes. It was determined that as the temperature increased to 473 K, the mole fraction solubility increased considerably from 0.02 × 10 −3 to 212.88 × 10 −3 (10600-fold). Calculation of the thermodynamic properties indicated an endothermic process, Δ sol H > 0, with relatively high Δ sol S values. Spectroscopic, thermal and chromatographic analyses established the IBP stability at subcritical conditions. In the second part of the study, the degradation of IBP in H2 O2 -modified subcritical was studied and the effect of each process variable was investigated. The optimum degradation of 88% was reached at an IBP concentration of 15 mg L −1, temperature of 250 °C, 105 min treatment time and 250 mM H2 O2 . The process was optimized by response surface methodology and a mathematical model was proposed and validated. Temperature was determined as the most influential parameter, followed by H2 O2 concentration. At temperatures higher than 230 °C, a small but noticeable reduction in degradation % suggested that the OH· radicals are consumed at a higher rate than they are produced, through side reactions with other radicals and/or IBP by-products. Finally, potential by-products were determined by gas chromatographic-mass spectrometric analysis and potential by-products were proposed. Graphical abstract: Image 1 Highlights: The aqueous solubility of ibuprofen increased 10600 times at 473 K. The isobaric heat capacity of the solution was determined as 70.28 J mol −1 ·K −1 . 89% degradation was achieved at a subcritical water temperature of 250 °C and 250 mM H2 O2 . Temperature was the most influential variable in degradation which followed first order kinetics.